Micelles versus Ribbons: how congeners drive the self-assembly of acidic sophorolipid biosurfactants - Dhasaiyan, Prabhu; Griel, Patrick Le; Roelants, Sophie; Redant, Emile; Bogaert, Inge N. A. Van; Prevost, Sylvain Francois; Prasad, Bhagavatula L. V.; Baccile, Niki (ChemPhysChem, 2017)
Sophorolipids (SLs), a class of microbially derived biosurfactants, are reported by different research groups to have different self-assembled structures (either micelles or giant ribbons) under the same conditions. Here we explore the reasons behind these contradictory results and attribute these differences to the role of specific congeners that are present in minute quantities. We show that a sample composed of a majority of oleic acid (C18:1) sophorolipid in the presence of only 0.5 % (or more) of congeners with stearic acid (C18:0) or linoleic acid (C18:2) results in the formation of micelles that are stable over long periods of time. Conversely, the presence of only 10 to 15 % of congeners with a stearic acid chain gives fibrillar structures instead of micelles. To study the mechanisms responsible, oleic acid SLs devoid of any other congeners were prepared. Very interestingly, this sample can self-assemble into either micelles or fibers depending on minute modifications to the self-assembly conditions. The findings are supported by light scattering, small-angle X-ray scattering, transmission electron microscopy under cryogenic conditions, high-pressure liquid chromatography, and NMR spectroscopy.

pH- and time-resolved in situ SAXS study of self-assembled twisted ribbons formed by elaidic acid sophorolipids - Dhasaiyan, Prabhu; Prevost, Sylvain; Baccile, Niki; Prasad, Bhagavatula L. V. (Langmuir, 2018)
Conditions that favor the helical structure formation in structurally similar sophorolipids (SLs), that is, elaidic acid SLs (having a trans double bond between the C9 and C10 positions of the alkyl chain) and stearic acid SLs (no double bond), are presented here. The helical self-assembled structures formed by elaidic acid SLs were independent of pH and also were mediated by a micellar intermediate. On the other hand, the stearic acid SLs formed helical structures under low pH condition only. Astonishingly, the formation routes were found to be different, albeit the molecular geometry of both SLs is similar. Even if a conclusive mechanistic understanding must await further work, our studies strongly point out that the noncovalent weak interactions in elaidic acid SLs are able to overcome the electrostatic repulsions of the sophorolipid carboxylate groups at basic pH and facilitating the formation of helical structures. On the other hand, the hydrophobic interactions in stearic acid SLs endow the helical structures with extra stability, making them less vulnerable to dissolution upon heating.

Antibacterial properties of glycosylated surfaces: variation of the glucosidal moiety and fatty acid conformation of grafted microbial glycolipids - Valotteau, Claire; Roelants, Sophie L. K. V.; Dhasaiyan, Prabhu; Zibek, Susanne; Guenther, Michael; Soetaert, Wim; Everaert, Bernd; Pradier, Claire-Marie; Babonneau, Florence; Baccile, Niki; Humblot, Vincent (Molecular Systems Design & Engineering, 2020)
Glycosylated surfaces can display antimicrobial properties. It has been shown that sophorolipids can be used to develop biocidal coatings against Gram-positive and Gram-negative bacteria, but with a limited efficiency so far. Therefore, it appears necessary to further investigate the surface antibacterial activity of a broader set of structurally related glycolipids. The present work explores the influence of the glucosidic moiety (gluco-, sophoro-, cellobio-) and the fatty acid backbone (saturated,cisortransmonounsaturated). We show that the fatty acid backbone plays an important role:cisderivative of sophorolipids (SL) grafted onto model gold surfaces has better biocidal properties than saturated (SL0) andtransmonounsaturated (SLt) molecules, which appear to be inefficient. The number of glucose units is also a key factor: a one-third decrease in antibacterial activity is observed when having one glucose unit (GL) compared to two (SL). Sugar acetylation (SLa) does not seem to have an impact on the biocidal properties of surfaces. These results are not limited to sophorolipids, with cellobioselipids (CL) leading to similar antibacterial observations.